SEBARAN SPASIAL KONDISI LINGKUNGAN HUTAN MANGROVE DI PESISIR PANTAI KOTA KUPANG - Jeriels Matatula; Erny Poedjirahajoe; Satyawan Pudyatmoko (Graduate School Bogor Agricultural University (SPs IPB), 2019)
Mangrove is a specific ecosystem, which commonly is in the small wave beach or covered from wave beach area, affected by the sea tidal and water fill from the land. The purpose of this research is to know the spatial spread of the mangrove habitat environmental factor (salinity, mud thickness and slope) at the Kupang seashore ( Paradiso, mangrove tourism and Oesapa). The salinity condition of the mangrove forest at Paradiso is low up to medium category, the mud thickness is slight, thick and very thick. The slope is 2%-2,66%. At the mangrove tourism location, the salinity is varied from the dominant range value 23,33% and 24,66%, mud thickness is 10,88 cm up to 51,33 cm, and the slope of 1%-3%. At Oesapa mangrove forest location, the salinity is between 10%-18%, the mud thickness is 21,55 cm – 49,22 cm, and the slope is 2%-3%. The environmental condition of the mangrove forest which is at Kupang seashore must be a model for the planning and the management of the mangrove forest in Kupang.